ChemInform Abstract: Ferroelectric InMnO3: Growth of Single Crystals, Structure and High‐Temperature Phase Transitions. Issue 40 (September 2016) - Bekheet, Maged F.; Svoboda, Ingrid; Liu, Na; Bayarjargal, Lkhamsuren; Irran, Elisabeth; Dietz, Christian; Stark, Robert W.; Riedel, Ralf; Gurlo, Aleksander
Abstract: Single crystals of InMnO3 are grown from equimolar mixtures of In2 O3 and Mn2 O3 in a PbF2 flux (Mo/Al2 O3 substrates, 950 °C, 60 h).